2000
DOI: 10.1037/h0087722
|View full text |Cite
|
Sign up to set email alerts
|

A multidimensional conceptualization of racism-related stress: Implications for the well-being of people of color.

Abstract: A conceptualization of racism-related stress and its impact on well-being is offered that integrates existing theory and research on racism, multicultural mental health, and the stress process. The conceptualization is relevant to diverse racial/ethnic groups, considers the larger social and historical context, and incorporates attention to culture-based variables that may mediate the relationship between racism and well-being. Implications for intervention are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

49
1,461
0
13

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,241 publications
(1,555 citation statements)
references
References 79 publications
49
1,461
0
13
Order By: Relevance
“…These findings are in line with several reviews and studies that have consistently suggested that experienced discrimination has a harmful psychological impact on those against whom it is directed (e.g., Brondolo et al, 2009b;Harrell, 2000;Harris et al, 2006: Krieger, 1999Paradies, 2006;Priest et al, 2012;Williams & Mohammed, 2009;2013a;2013b).…”
Section: Discussionsupporting
confidence: 90%
“…These findings are in line with several reviews and studies that have consistently suggested that experienced discrimination has a harmful psychological impact on those against whom it is directed (e.g., Brondolo et al, 2009b;Harrell, 2000;Harris et al, 2006: Krieger, 1999Paradies, 2006;Priest et al, 2012;Williams & Mohammed, 2009;2013a;2013b).…”
Section: Discussionsupporting
confidence: 90%
“…Identity can inform beliefs about interpersonal and institutional interactions, and there is evidence that racial identity is an influential construct in the experience of racial discrimination [4][5][6]. Racial identity has been found to buffer the adverse effects of acute and chronic discrimination on health problems for African Americans [7] perhaps by increasing feelings of social support and thus enhancing an individual's capacity to cope and respond to stressful experiences (e.g., [1]).…”
Section: Introductionmentioning
confidence: 99%
“…Restringindo-se ao racismo e seus efeitos deletérios sobre a saúde, Harrell (2000) conceituou o estresse como relações entre indivíduos ou grupos e seu ambiente, das quais emergem significações da dinâmica do racismo, que são percebidas como algo que excede ou sobrecarrega os recursos individuais ou coletivos disponíveis para a adaptação, ou que ainda ameaçam a autopercepção de bem-estar psicológico. Com esse parâmetro, é sabido que a discriminação racial cria limitações fundamentais na vida dos indivíduos, implicando em maiores ameaças diretas ou contingentes, o que afeta o senso de integridade individual e impacta incisivamente sobre a quantidade de estresse experienciada ( Dentre as formas de discriminação mais conhecidas, o racismo é frequentemente relacionado nos estudos envolvendo a saúde das populações, sendo incorporado por diversos modelos enquanto variável explicativa do status de saúde (Caldwell et al, 2006;Clark et al, 1999;Geiger, 2006;Mullings & Schulz, 2006;Nazroo & Williams, 2006;Pieterse & Carter, 2007;Whaley, 1998).…”
Section: Racismo E Saúde: Achados a Partir Da Teoria Do Estresseunclassified
“…O racismo fornece o contexto necessário para a criação e manutenção de estereótipos, preconceitos e discriminação, visto ser fomentado por um histórico de injustiça e sustentação da desigualdade, estando ligado a estressores persistentes que minam cronicamente a capacidade de adaptação, ajuste social e sensação de bem-estar dos indivíduos (Harrell, 2000). Na tentativa de delinear um modelo compreensivo de como o racismo afeta a saúde, para Krieger (2003) o racismo impacta em seis dimensões: 1) Acentua a escassez de recursos econômicos e sociais; 2) Causa maior exposição a fatores nocivos e tóxicos, como por exemplo, empregos de menor qualificação e maior risco; 3) É facilitador de conjecturas sociais que provocam danos à saúde; 4) Provê inadequados cuidados e acesso à saúde; 5) Potencializa a ocorrência de experiências agressoras motivadas pela discriminação ou violência; 6) Induzem com maior frequência a autopercepção de saúde de indivíduos expostos ao racismo como deteriorada.…”
Section: Racismo E Saúde: Achados a Partir Da Teoria Do Estresseunclassified
See 1 more Smart Citation